Pan-Canadian consensus recommendations for proton beam therapy access in Canada. (November 2022) - Mitera, Gunita; Tsang, Derek; McCurdy, Boyd; Goddard, Karen; Ebacher, Annie; Craig, Tim; Greenland, Jonathan; Kentish, Staci; Koul, Rashmi; Logie, Natalie; Morneau, Mélanie; Morrison, Andra; et al.
Highlights: The first pan-Canadian recommendations created to support equitable and timely access to quality proton therapy. Input from experts across Canada, external peer-review, and community consultation included. 27 consensus recommendations developed for patient eligibility, program and system levels. Abstract: Purpose: Proton Beam Therapy (PBT) is a treatment option for select cancer patients. It is currently not available in Canada. Assessment and referral processes for out-of-country treatment for eligible patients vary by jurisdiction, leading to variability in access to this treatment for Canadian cancer patients. The purpose of this initiative was to develop a framework document to inform consistent and equitable PBT access for appropriate patients through the creation of pan-Canadian PBT access consensus recommendations. Materials and methods: A modified Delphi process was used to develop pan-Canadian recommendations with input from 22 PBT clinical and administrative experts across all provinces, external peer-review by provincial cancer and system partners, and feedback from a targeted community consultation. This was conducted by electronic survey and live discussion. Consensus threshold was set at 70% agreement. Results: Four consensus rounds resulted in a final set of 27 recommendations divided into three categories: patient eligibility (n = 9); program level (n = 10); and system level (n = 8). Patient eligibility included: anatomic site (n = 4), patient characteristics (n = 3), clinical efficacy (n = 2). Program level included: regulatory and staff requirements (n = 5), equipment and technologies (n = 4), quality assurance (n = 1). System level included: referral process (n = 5), costing, budget impact and quality adjusted life years (n = 2), eligible patient estimates (n = 1). Recommendations were released nationally in June 2021 and distributed to all 43 cancer programs in Canada. Conclusion: A pan-Canadian consensus-building approach was successful in creating an evidence-based, peer-reviewed suite of recommendations that support application of consistent clinical criteria to inform treatment options, facility set-up and access to high quality proton therapy.